Indeks Kualitas Perairan dan Fitoplankton Periode Ramadan di Situ Gintung, Tangerang Selatan, Banten - Yayan Mardiansyah Assuyuti; Alfan Farhan Rijaluddin; Firdaus Ramadhan (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The behavior of the Indonesian Muslim community has changed in the month of Ramadan and will affect the anthropogenic waste that enters the lake ecosystem. The study was conducted in Situ Gintung Lake, South Tangerang City, in the period before (BR), time (DR) and after (AR) Ramadan 2015. The aims of study was to determine (i) the chemical, physical and water quality using the water quality index (WQI), (ii) phytoplankton classification using codons, pollution and Saprobit indices and (iii) the correlation of chemical and physical of waters with phytoplankton. Water temperature, transparency, TDS and conductivity have significant differences (ANOVA, p < 0.05) in all periods except pH, DO and NPP (p > 0.05) with WQI was a medium to good categories. Classification of phytoplankton codons, algae and Saprobit pollution indices values ​​showed that Situ Gintung had meso to eutrophic categories and showed contamination in all periods, respectively. Canonical Correspondence Analysis (CCA) shows that phytoplankton correlate with BOD5.